Perioperative bridging anticoagulation during dabigatran or warfarin interruption among patients who had an elective surgery or procedure: substudy of the RE-LY trial - Douketis, James D.; Brückmann, Martina (Thrombosis and haemostasis, 2015)
In patients with atrial fibrillation (AF) who require interruption of dabigatran or warfarin for an elective surgery/procedure, the risks and benefits of perioperative bridging anticoagulation is uncertain.We accessed the database from RE-LY, a randomised trial comparing dabigatran with warfarin for stroke prevention in AF, to assess the potential benefits and risks of bridging. In patients who had a first interruption of dabigatran or warfarin for an elective surgery/procedure, we compared the risk for major bleeding (MB), stroke or systemic embolism (SSE) and any thromboembolism (TE) in patients who were bridged or not bridged during the period of seven days before until 30 days after surgery/procedure. We used multivariable Cox regression to adjust for potential confounders.Bridging was used more during warfarin interruption than dabigatran interruption (27.5 % vs 15.4 %; p< 0.001). With dabigatran interruption, bridged patients had more MB (6.5 % vs 1.8 %, p< 0.001) than those not bridged but bridged and not bridged groups did not differ for any TE (1.2 % vs 0.6 %, p=0.16) and SSE (0.5 % vs 0.3 %, p=0.46). With warfarin interruption, bridged patients had more MB (6.8 % vs 1.6 %, p< 0.001) and any TE (1.8 % vs 0.3 %, p=0.007) than those not bridged but bridged and not bridged groups did not differ for SSE (0.5 % vs 0.2 %, p=0.321). In conclusion, in patients who interrupted dabigatran or warfarin for a surgery/ procedure in the RE-LY trial, use of bridging anticoagulation appeared to increase the risk for major bleeding irrespective of dabigatran or warfarin interruption.